Reformulation of pizza crust in restaurants may increase whole-grain intake among children. Issue 8 (26th August 2014) - Tritt, Aimee; Reicks, Marla; Marquart, Len
Abstract: Objective: Whole-grain intake among children is well below recommendations. The purpose of the present study was to test the acceptability and liking of pizza made with whole-grain crust compared with refined-grain crust among children in restaurant and school settings. Design: Plate waste data were collected via observation from child restaurant patrons consuming pizza made with either whole-grain or refined-grain crust. Waste was estimated by trained observers over eight months (August 2012–March 2013). Percentage waste was calculated and compared by crust type. A taste test was conducted with school children who tasted pizza made with whole-grain crust alongside pizza made with refined-grain crust and rated their liking of each product. Liking ratings were compared by crust type. Setting: Five Green Mill restaurant (a Midwest US chain) locations and one elementary school in the Minneapolis/St. Paul metropolitan area, Minnesota, USA. Subjects: Child restaurant patrons ( n 394) and school children ( n 120, grades 3–5). Results: Children consumed as much of the pizza made with whole-grain crust (42·1 %) as the pizza made with refined-grain crust (44·6 %; P =0·55), based on an average serving size of 350–400 g. Liking ratings for both types of pizza were high (>4·5 of 5) and did not differ by crust type ( P =0·47). Conclusions: These positive consumption and liking outcomes indicate that whole-grain pizza crust is well accepted among children in a restaurant setting. The impact on whole-grain intake could be substantial if large, national restaurant chains served pizza made with whole-grain crust.